One health environmentalism - Capps, Benjamin (Cambridge elements, 2024)
One Health emerges from the contingent scientific, social, and political realities of environmentalism. The concept mixes the land, sea, and sky with geopolitics on the global stages of the United Nations and World Health Organization. It inspires new investment in conservation and public health, motivates interdisciplinary collaboration, and in practice implicates green economies and animal law as well. This Element does not tackle all of this but attempts to situate One Health in the catastrophe of COVID-19; a socio-ecological upheaval prophetic of the inevitable next pandemic evolving from planetary climate crisis of our own making. One Health Environmentalism argues that humanity's future depends upon extending an olive branch to biotic communities, by being less speciesist and less blind to the rights in nature